2023
DOI: 10.3390/pr11071879
|View full text |Cite
|
Sign up to set email alerts
|

Do the True Boiling-Point Distillation Yields of Crude Oil Blends Obey the Additive Blending Rule?

Abstract: Twelve crude oil blends prepared from seven individual crude oils and an imported atmospheric residue were characterized through a true boiling point (TBP) distillation analysis and their density. When comparing the measured TBP fraction yields with those estimated through the application of the additive blending rule, it was found that, for four crude oil blends, the additive blending rule was valid, while for the remaining eight crude oil blends, deviations of the measured TBP yields from the estimated ones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 22 publications
3
6
0
Order By: Relevance
“…The data to calculate the ASTM D 86 boiling fraction volumetric yield up to 240 • C were used from Table S2 (the composition of petroleum blend) and from Table S5 (ASTM D 86 distillation data of crude oils Urals, Light Siberian, and BTV). The data presented in Figure 3 are in line with the results reported in [44][45][46] showing that the crude oil blend distillation characteristics may not be additive for some oil mixtures. In this case, the crude mixture 67% Urals/33% BTV obviously does not follow the linear blending additive rule.…”
Section: Laboratory Oil Test Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The data to calculate the ASTM D 86 boiling fraction volumetric yield up to 240 • C were used from Table S2 (the composition of petroleum blend) and from Table S5 (ASTM D 86 distillation data of crude oils Urals, Light Siberian, and BTV). The data presented in Figure 3 are in line with the results reported in [44][45][46] showing that the crude oil blend distillation characteristics may not be additive for some oil mixtures. In this case, the crude mixture 67% Urals/33% BTV obviously does not follow the linear blending additive rule.…”
Section: Laboratory Oil Test Resultssupporting
confidence: 88%
“…In our recent study [44], where 12 crude oil blends were investigated using TBP distillation apparatus, it was shown that for the petroleum blends which deviate from the linear blending rule, the molar excess volume correlates with the difference between the measured TBP yield and the calculated one using the linear blending rule. Having in mind that the TBP fraction yields correlate with ASTM D 86 distillation yields (Equations (S1)-(S6)), we decided to test the validity of the relation established in [44] between the molar excess volume and the difference between measured and calculated ASTM D 86 boiling fraction volumetric yield up to 240 • C following the linear blending rule. For that purpose, ASTM D-86 distillation characteristics of four crude oils investigated in [44], namely Iranian Heavy (IHCO), Sirtica, Russian Export Crude blend (REBCO), and Arabian medium (AMCO) (shown in Table S6), were used to calculate the ASTM D 86 boiling fraction volumetric yields up to 240 • C following the linear blending rule of their blends: IHCO:SIRTICA = 1:2; IHCO:SIRTICA = 1:1; IHCO:SIRTICA = 2:1; REBCO:AMCO = 1:2; REBCO:AMCO = 1:1; and REBCO:AMCO = 2:1.…”
Section: Laboratory Oil Test Resultsmentioning
confidence: 99%
See 3 more Smart Citations